2019
DOI: 10.1111/jgh.14603
|View full text |Cite
|
Sign up to set email alerts
|

Colonic diverticular bleeding and predictors of the length of hospitalization: An observational study

Abstract: Background and Aim A significant percentage of patients with colonic diverticular bleeding (CDB) experience bleeding that is severe enough to necessitate prolonged hospitalization. Prolonged hospitalization causes deterioration in patients' quality of life, as well as difficulties with cost‐effective utilization of medical resources, and is a financial burden to the society. Therefore, we investigated the factors associated with the length of hospitalization for the optimal management of patients hospitalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…Our study revealed a shorter length of hospitalization in the urgent colonoscopy group, which was consistent with the findings of previous reports 7,19,21 . This may only reflect that urgent colonoscopy allows physicians to recognize patients' condition and decide on the therapeutic strategy, which contributes to an earlier discharge from hospital.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study revealed a shorter length of hospitalization in the urgent colonoscopy group, which was consistent with the findings of previous reports 7,19,21 . This may only reflect that urgent colonoscopy allows physicians to recognize patients' condition and decide on the therapeutic strategy, which contributes to an earlier discharge from hospital.…”
Section: Discussionsupporting
confidence: 92%
“…According to previous studies, the efficacy of urgent colonoscopy for CDB was controversial. One retrospective study reported that urgent colonoscopy shortened the length of admission for CDB 7 . Similar randomized control trial studies, which targeted LGB rather than CDB, reported inconsistent results regarding the efficacy of urgent colonoscopy in terms of the length of hospital stay, blood transfusion, re‐bleeding, and surgery 9–11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available evidence comparing early vs. elective colonoscopy in the management of patients with acute LGIB consists of seven systematic reviews with meta-analyses [55][56][57][58][59][60][61], four RCTs [51,[62][63][64], and 16 observational studies [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] (Table 7 s). Patients with "minor" LGIB managed as outpatients and patients with an UGIB source were excluded from the RCTs [51,[62][63][64] and most of the observational studies [66,67,69,[71][72][73][74][75][76][77][78].…”
Section: What Is the Appropriate Timing For Colonoscopy In Patients With Acute Lower Gastrointestinal Bleeding?mentioning
confidence: 99%
“…We considered the certainty of evidence to be low, despite the significant number of studies evaluating the appropriate timing of colonoscopy. All but one [80] of the observational studies were retrospective [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79], and the definitions and selection criteria were heterogeneous. All RCTs were nonblinded, with some concerns regarding bias (Tables 7 s and 8 s), and two trials were terminated before reaching the pre-planned sample size [51,63].…”
Section: Recommendationmentioning
confidence: 99%